COVID‐19‐associated AMPA‐R and CRMP‐5 autoimmune encephalitis in a patient with thymoma and myasthenia gravis - Jenelle Raynowska; Victoria Wu; Max Kazer; Jamie Nicole LaBuzetta; Dominic Ferrey; Anastasie Dunn‐Pirio (Clinical Case Reports)
Abstract Thymomas are associated with autoimmune disease, most commonly myasthenia gravis, and rarely with autoimmune encephalitis. More recently, viral triggers including COVID‐19 have also been implicated in autoimmunity. We present a case of antibody‐positive autoimmune encephalitis that developed in the setting of COVID‐19 in a patient with thymomatous myasthenia gravis.